The Impact of COVID-19 on Electricity Generation : An Empirical Investigation - Shen, Chang; Alberini, Anna; Timilsina, Govinda (Washington, DC : World Bank, 2022)
During the 2020-2022 period, the COVID Pandemic affected, directly or indirectly, every economic sector globally. While the effects on some sectors, such as travel and tourism, were highly visible, those on other sectors, such as utility services, require investigation. Whether COVID-19 affected total electricity generation and the electricity supply mix is an empirical question, which this study attempts to answer using panel data of daily electricity generation between January 2018 and September 2021 from 26 countries. The study finds that a 1-unit increase in the stringency measure of COVID-19 is linked with a 463 MWh decrease in the total daily electricity generation. The study does not find a significant change in the electricity generation mix due to COVID-19 responses, although there is some evidence of some substitution of wind with solar and coal with natural gas.